When Victims Become Suspects: Legal Aspect of Criminalization on Amaq Sinta Case of Spoliation - Erhuma, Ahmed; Maulana, Ahmad; Naron, Phassakorn (Faculty of Law, Universitas Negeri Semarang, 2023)
In recent months, a controversial incident has stirred public discourse, wherein a victim of a